Impact of solid content on hydrothermal pretreatment of municipal sludge prior to fermentation and anaerobic digestion. (December 2022) - Kakar, Farokh Laqa; Liss, Steven N.; Elbeshbishy, Elsayed
Abstract: This study investigated the impact of the solid sludge content concentrations (SC) on hydrothermal pretreatment (HTP) before fermentation and anaerobic digestion. Five different SC of 3.5%, 7%, 10%, 12%, and 16% were investigated in two different scenarios. The first scenario entailed using only the pretreated samples as substrates, whereas in scenario two, the substrates included pretreated samples combined with the supernatant. Results revealed that the highest overall pCOD solubilization (considering HTP and fermentation) of 64% was achieved for the sample with 12% SC combined with supernatant. The maximum volatile fatty acids production of 2.8 g COD/L occurred with 10% SC without supernatant. The maximum methane yield of 291 mL CH4 /g VSS added was attained at 7% SC without supernatant. Furthermore, the results indicated that increasing the SC beyond 7% in scenario 1 and 10% in scenario two led to a decrease in methane yield. Additionally, optimizing for all desired endpoints may be difficult, and there are limits on the increase in SC concerning methane production. Graphical abstract: Image 1 Highlights: Effect of solids content on thermal pre-treatment was investigated. High solids content had positive effect on the processes for resource recovery. High solids content had positive effect on the fermentation and anerobic digestion. The highest VFAs and methane yields was achieved at Solids content of 10%.